Translations of Yakub Kolas and Yanka Kupala poems into the Kazakh language: a contrastive-semantic aspect - Аmalbekovа М.Б.; Hirutski А.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
There is carried out a contrastive-semantic analysis of transla-tions of individual poems by the classics of Belarusian literature Y. Kolas and Y. Kupala. The article reveals general and specific features in the content of originals and translations at the level of individual lexemes, sentences, and stanzas. There have been established translation transformations (lexical, grammatical substitutions, permutations, additions, omissions, etc.), stylistic expedients (inversions, metaphorizations, synonyms) used in translation. The authors have noted some translation inaccuracies. It is concluded that, the translations of Belarusian poetry into the Kazakh language are accurate and pragmatically adequate. Sometimes the Kazakh text is more dynamic, expressive in comparison with the original. It is largely de-termined by both specifics of the language systems of the two languages and the personality of the translator